54.3k views
5 votes
5(x-3)-4(x-3) is equivalent to

User Riza Khan
by
5.3k points

1 Answer

4 votes

Answer:


5\left(x-3\right)-4\left(x-3\right)=x-3

Explanation:

Given the expression


5\left(x-3\right)-4\left(x-3\right)

solving the expression


5\left(x-3\right)-4\left(x-3\right)=5x\:-\:15\:-\:4x\:+\:12


= x - 3

Thus, the equivalent expression is


5\left(x-3\right)-4\left(x-3\right)=x-3

User Mjwunderlich
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.